Enhancing Holistic Value in Human Transformative Service through Religious Interaction Capability - Ken Sudarti; Hendar Hendar; Nabila Tharrazana (Media Ekonomi dan Manajemen, 2024)
This research investigates the impact of Interaction Capability on Customer Participation, influencing the development of Perceived Holistic Value in transformative human services aimed at enhancing customer well-being. An innovative aspect introduced in this study is Religious Interaction Capability, which supplements the existing dimensions of Interaction Capability: Individualized Interaction, Relational Interaction, Empowered Interaction, and Ethical Interaction Capability. The study involved 192 outpatient participants from Islamic hospitals in Central Java, Indonesia, selected through purposive sampling. Data analysis utilized Structural Equation Modeling (SEM) with AMOS 22.0. The results suggest that Religious Interaction Capability and other interaction capabilities significantly motivate religiously oriented patients to seek and responsibly share information. Furthermore, all factors facilitating Customer Participation contribute to the formation of Perceived Holistic Value, extending beyond transactional aspects such as process and outcome value to include a broader dimension of religious value. These findings have implications for strengthening the Resource-based View theory.